Diversity and Ecophysiological Performance of Coffee under Dry-Field and Homegarden Agroforestry in Yogyakarta - Mursyid, Harsanto; Suryanto, Priyono; Fadhilla, Suri; Silmia, Betha; Wibowo, Febri Arif Cahyo (Jurnal Sylva Lestari, 2025)
Coffee is commonly cultivated under agroforestry systems, including dry-field and homegarden. These systems were differentiated based on their proximity to the settlements, which might influence the species composition. This study aimed to observe plant composition, diversity, vegetation structure, and microclimate in coffee agroforestry systems and the physiological conditions of coffee. The experimental design was based on purposive sampling. A total of 100 nested plots were established in Glagaharjo and Balerante of Yogyakarta, each consisting of a dry-field and homegarden. Higher diversity and potential products were observed in dry-field agroforestry. There was no significant difference in microclimate between both systems. However, a significantly higher number of poles (p < 0.001) and trees (p < 0.001) in dry-field compared to homegarden contributed to lower light interception, higher humidity and temperature in dry-field, which could be associated with the higher physiological performance of coffee despite the non-significant difference between the systems (p > 0.05). Therefore, microclimate conditions under dry-fields were considered suitable for improving coffee growth performance.   Keywords: agroforestry, coffee, dry-field, eco-physiology, homegarden